Minireview: the role of nuclear receptors in photoreceptor differentiation and disease - Forrest, Douglas; Swaroop, Anand (Molecular endocrinology (Baltimore, Md.), 2012)
Rod and cone photoreceptors are specialized sensory cells that mediate vision. Transcriptional controls are critical for the development and long-term survival of photoreceptors; when these controls become ineffective, retinal dysfunction or degenerative disease may result. This review discusses the role of nuclear receptors, a class of ligand-regulated transcription factors, at key stages of photoreceptor life in the mammalian retina. Nuclear receptors with known ligands, such as retinoids or thyroid hormone, together with several orphan receptors without identified physiological ligands, complement other classes of transcription factors in directing the differentiation and functional maintenance of photoreceptors. The potential of nuclear receptors to respond to ligands introduces versatility into the control of photoreceptor development and function and may suggest new opportunities for treatments of photoreceptor disease.